A desmoid tumor with fluorodeoxyglucose accumulation arising from the anastomotic site of postoperative gastric cancer: a case report - Kento Kawashima; Kazuhiro Hiramatsu; Takehito Kato; Masahide Fukaya; Taro Aoba; Atsuki Arimoto; Takayuki Yamaguchi (Journal of Medical Case Reports, 2022)
Abstract Background Desmoid tumors are extremely rare borderline benign and malignant tumors that do not exhibit accumulation on fluorodeoxyglucose positron emission tomography–computed tomography. In the present study, we report a rare case of a desmoid tumor with fluorodeoxyglucose accumulation at the anastomotic postoperative gastric cancer site. Case presentation A 68-year-old Japanese man underwent robot-assisted laparoscopic distal gastrectomy for early-stage gastric cancer in 2019. The pathological diagnosis was stage IA cancer, and no adjuvant chemotherapy was administered. Two years after surgery, a soft mass appeared on the greater curvature side of the anastomosis on computed tomography. Fluorodeoxyglucose positron emission tomography–computed tomography revealed fluorodeoxyglucose accumulation, which suggested a malignancy; therefore, surgery was performed for diagnostic treatment. The histopathological findings led to the diagnosis of a desmoid tumor. The patient has not experienced recurrence to date. Conclusions In the present study, we encountered a desmoid tumor arising from the anastomotic site of a postoperative gastric cancer. This case is rare as fluorodeoxyglucose positron emission tomography–computed tomography showed fluorodeoxyglucose accumulation in the desmoid tumor, and a preoperative diagnosis could not be reached. We hope that further studies will improve the accuracy of preoperative diagnosis.